The Leap of Your Life - Baker, Tommy (Ascent Audio, 2019)
There's a bold decision in your life you've been waiting to make, and every day passing by is a reminder of what hasn't happened. Conveniently tucked in a box labeled "someday," the fear of the unknown has taken a grip on your life and put your dreams on hold. Until now. Whether your leap is quitting the soul sucking job and starting your own business, taking a bold chance on love or finally going all in on your dreams, The Leap of Your Life is the ticket to get you there. All while having the time of your life and ensuring you don't wake up years down the line with a sinking feeling of regret. Author and high-performance coach Tommy Baker has helped thousands of everyday people identify and take their leap, step into courage, and create a life they can't wait to wake up for. After interviewing 250+ of the world's most powerful entrepreneurs, thought leaders, experts, spiritual teachers, and athletes he discovered a common theme: They all took a leap, even if they were full of fear-and it radically transformed their experience of life.
Online resource; Title from title page (viewed May 21, 2019)
Keywords: Self-help; Audiobooks